2023
DOI: 10.1002/hsr2.1258
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries in Rwanda: A scoping review

Abstract: Background and Aims Dental caries is an infectious disease affecting virtually all nations, including Rwanda. In Rwanda, the burden of dental caries is an issue of public health concern. To ensure the progressive eradication of the current dental caries burden in Rwanda through an evidence‐based approach, it is imperative to have an overview of the scientific research landscape of dental caries in the country. This study—a scoping review—aims to review the available evidence and gaps on dental car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(140 reference statements)
0
1
0
Order By: Relevance
“…al., 2015). In Rwanda, an analytical study revealed a high prevalence of dental caries ranging from 42.42% to 71.5%, (Kehinde et al, 2023) In Uganda, a study done out of 239 participants indicated that the prevalence of dental caries is 71.6% and the need for treatment was 100% (Wilfred, Arubaku & Maling, 2022). A community-based oral health survey showed that the most common determinants of oral disease as reported by key informants were; Sugar consumption, failure to use fluoride toothpaste, lack of access to fluorinated water, tobacco use, lack of community oral health education, use of traditional practices, Low levels of community awareness and failure to have oral health checkups (National oral health policy-MOH,2018).…”
Section: Background Of the Studymentioning
confidence: 99%
“…al., 2015). In Rwanda, an analytical study revealed a high prevalence of dental caries ranging from 42.42% to 71.5%, (Kehinde et al, 2023) In Uganda, a study done out of 239 participants indicated that the prevalence of dental caries is 71.6% and the need for treatment was 100% (Wilfred, Arubaku & Maling, 2022). A community-based oral health survey showed that the most common determinants of oral disease as reported by key informants were; Sugar consumption, failure to use fluoride toothpaste, lack of access to fluorinated water, tobacco use, lack of community oral health education, use of traditional practices, Low levels of community awareness and failure to have oral health checkups (National oral health policy-MOH,2018).…”
Section: Background Of the Studymentioning
confidence: 99%